Attitudes toward and management of fibromyalgia: a national survey of Saudi Arab’s medical practitioners - Mubaraki, Adnan Ali; Abdulaziz, Reham Ahmed; Altalhi, Thekra Matoq; Kabrah, Lama Kamal; Althagafi, Atheer Musaad; Alsufyani, Raghad Ali; Althubaiti , Shahad Waslallah (Journal of the Pakistan Medical Association, 2023)
Widespread pain is characteristic of fibromyalgia. Patients consult different specialities, and hence, diagnosis and treatment is often delayed. To evaluate and assess the attitudes and management of fibromyalgia among medical practitioners in Saudi Arabia a cross-sectional study was conducted through an online questionnaire in November 2021. Screening demographics included age, sex, place of work, speciality, year of graduation, and practical experience. Questions about fibromyalgia (general knowledge and management, ACR criteria 2010, essential symptoms, diagnosis, and treatment) were also part of the questionnaire. There were 103 respondents, out of which 88(85.4%) have heard about fibromyalgia and 21(20.4%) had managed cases of fibromyalgia, while 32(31.1%) knew about the 2010 ACR diagnostic criteria. Commonest reported characteristics of fibromyalgia were excessive fatigue 74(71.8%), widespread pain 71(68.9%), weakness 54(52.4%), and sleep disturbance 38(36.9%). About 76(73.8% reported it is a clinical diagnosis and 75(72.6%) reported having the knowledge about the treatment of fibromyalgia. —Continue